Taurine Supplementation Increases Post-Exercise Lipid Oxidation at Moderate Intensity in Fasted Healthy Males - Carvalho, Milena Barbon de [UNESP]; Cunha Brandao, Camila Fernanda; Fassini, Priscila Giacomo; Bianco, Thiago Mantello; Batitucci, Gabriela [UNESP]; Martinez Galan, Bryan Steve [UNESP]; De Carvalho, Flavia Giolo; Vieira, Tales Sambrano [UNESP]; Ferriolli, Eduardo; Marchini, Julio Sergio; Ramos da Silva, Adelino Sanchez; Freitas, Ellen Cristini de [UNESP] (Mdpi, 2020)
Based on the fact that taurine can increase lipid metabolism, the objective of the present study was to evaluate the effects of different doses of acute taurine supplementation on lipid oxidation levels in healthy young men after a single bout of fasting aerobic exercise. A double-blind, acute, and crossover study design was conducted. Seventeen men (age 24.8 +/- 4.07y; BMI: 23.9 +/- 2.57 kg/m(2)) participated in the present study. Different doses of taurine (TAU) (3 g or 6 g) or placebo were supplemented 90 min before a single bout of fasting aerobic exercise (on a treadmill at 60% of VO2 max). The subjects performed three trials, and each one was separated by seven days. Blood samples were collected at baseline and after the exercise protocol of each test to analyze plasma levels of glycerol and taurine. Lipid and carbohydrate oxidation were determined immediately after exercise for 15 min by indirect calorimetry. We observed that TAU supplementation (6 g) increased lipid oxidation (38%) and reduced the respiratory coefficient (4%) when compared to the placebo (p < 0.05). However, no differences in lipid oxidation were observed between the different doses of taurine (3 g and 6 g). For glycerol concentrations, there were no differences between trials. Six grams of TAU supplementation 90 min before a single bout of aerobic exercise in a fasted state was sufficient to increase the lipid oxidation post-exercise in healthy young men.
Keywords: Aerobic exercise; fasting; fat oxidation; glycerol; supplementation; taurine